Blood Zinc Profile and Fecal Analysis of Colitis Patients in Cipto Mangunkusumo General Hospital - Indrasari, Nuri Dyah; Pattiasina, Firensca; Fauzi, Achmad; Yusra, Yusra; Kumalawati, July; Immanuel, Suzanna (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2022)
Background: Colitis is a gastrointestinal disease that poses a major problem in Indonesia. Zinc (Zn) is an important trace element which plays role as antimicrobial in intestinal mucosa, increases gastrointestinal barrier, and immune function. Colitis can cause histologic changes in gastrointestinal tract epithelial which will disrupt the absorption and excretion of Zn causing zinc deficiency. This study aims to evaluate the difference of Zn level in colitis and healthy subjects, as well as the fecal analysis profile of colitis patients in Cipto Mangunkusumo General Hospital. Method: The design of this study was cross-sectional and was performed in colitis and healthy subjects. Colitis patients were recruited consecutively in patients in Gastroenterology Clinic and Gastrointestinal Endoscopy Centre in Cipto Mangunkusumo General Hospital. Zinc examination from blood sample was performed using spectrophotometry. Fecal analysis was performed manually. The level of zinc from colitis subjects was compared to healthy subjects. Fecal analysis examination consists of macroscopic, microscopic, and chemical examinations of the feces.Results: There were 40 colitis subjects and 16 healthy subjects in August 2019 - May 2020. There were significant differences in Zn levels between colitis and healthy subjects, which were 10.9 ± 1.9 mol/L and 12.3 ± 1 mol/L, respectively (p = 0.011). There were 45% (18/45) colitis subjects who were also suffering from Zn deficiency. The stool analysis in colitis subjects showed soft stool consistency in 90% subjects, slimy stools in 17.5%, increased in erythrocyte count in 60%, increased in leukocyte count in 5%, positive stool starch in 20%, positive stool fat in 7.5%, acid pH in 97.5%, positive stool occult blood in 37.5%, and fungi in stool in 7.5%.